The Operative management in Bariatric Acute abdomen (OBA) Survey: long-term complications of bariatric surgery and the emergency surgeon's point of view - De Simone, B; Ansaloni, L; Sartelli, M; Kluger, Y; Abu-Zidan, FM; Biffl, WL; Heyer, A; Coccolini, F; Baiocchi, GL; Catena, F; Campanile, FC; Mario, D; et al. (Bmc, 2024)
Background The number of bariatric procedures is increasing worldwide. No consensus or guidelines about the emergency management of long-term complications following bariatric surgery are currently available. The aim of this study is to investigate by a web survey how an emergency surgeon approaches this unique group of patients in an emergency medical scenario and to report their personal experience. Method An international web survey was sent to 197 emergency surgeons with the aim to collect data about emergency surgeons' experience in the management of patients admitted in the emergency department for acute abdominal pain after bariatric surgery. The survey was conceived as a questionnaire composed by 26 (multiple choice and open) questions and approved by a steering committee. Results One hundred seventeen international emergency surgeons decided to join the project and answered to the web survey with a response rate of 59.39%. Conclusions The aim of this WSES web survey was to highlight the current management of patients previously submitted to bariatric surgical procedures by ES. Emergency surgeons must be mindful of postoperative bariatric surgery complications. CT scan with oral intestinal opacification may be useful in making a diagnosis if carefully interpreted by the radiologist and the surgeon. In case of inconclusive clinical and radiological findings, when symptoms fail to improve, surgical exploration for bariatric patients presenting acute abdominal pain, by laparoscopy if expertise is available, is mandatory in the first 12-24 h, to have good outcomes and decrease morbidity rate.